Aktivitas Antioksidan, Kadar Air, dan Sifat Sensoris Teh Susu Daun Binahong dengan Variasi Lama Pengeringan - fatimah, Nur aini; dr, Nurrahman; Hersoelistyorini, wikanastri (Universitas Muhammadiyah Semarang, 2024)
Herbal tea is a processed product of plant parts that do not come from tea leaves (Inti, 2008). One herbal tea is tea from binahong leaves. Binahong leaf tea contains flavonoids. Flavonoids have a role as antioxidants and antimicrobials. The flavonoid content has bitter and astringent properties which can affect the taste. Milk tea is an innovative tea with the addition of milk. Processing binahong leaves into milk tea aims to reduce the bitter and astringent taste. Milk tea has a savoury and sweet taste. The main objective of this research is to examine the effect of drying time on antioxidant activity, water content, and sensory properties of binahong leaf milk tea. The research method was experimental using a Completely Randomized Design (CRD) with 6 treatments and 5 replications. The stages carried out are making binahong leaf tea, making binahong leaf powder tea, and making binahong leaf milk tea. Then analyzed the antioxidant activity, water content, and sensory properties (colour, taste, aroma). Variations in drying time (0, 180, 240, 300, 360, and 420 minutes). Based on the research results, show that variations in drying time affect antioxidant activity, water content, and sensory properties (colour and taste), but do not affect the aroma of binahong leaf milk tea. The best treatment was found to be a variation of drying time of 420 minutes with antioxidant activity values (52.84% RSA), water content (2.88%), and hedonic (3.23).